INFLUENCE OF SELF-EFFICACY AND ORGANIZATIONAL EXPERIENCE OF STUDENT’S WORK READINESS - Dwiriyanto, Muhammad Daffa; Sumiati, Ati; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research aims to analyze the influence of self-efficacy and organizational experience of the work readiness of students at Universitas Negeri Jakarta. The research method implemented in this study is a quantitative method, with surveys as the method of collecting samples. The known population in this study consists of 364 students from the Faculty of Economics at Universitas Negeri Jakarta, representing various study programs as the accessible population. The sample was determined using the proportional random sampling method with a 5% margin of error, resulting in a total of 177 students. The data analysis technique used in this research is multiple regression analysis. The results of this research show that self-efficacy has an influence on a student’s work readiness, organizational experience also has an influence on a student’s work readiness, and self-efficacy and organizational experience simultaneously influence a student’s work readiness.